Nitrogen Release Patterns From Deep Placement Sites of Urea in a Wetland Rice Soil - Savant, N.K.; De Datta, S.K. (Wiley, 1979)
Release patterns of N from deep placement sites of prilled urea (PU), supergranule urea (SGU), sulfur‐coated urea (SCU), and urea in mudball (MBU) were studied in in situ wetland Maahas clay at the International Rice Research Institute. Nitrogen release from PU and SGU was rapid during first day after placement and decreased thereafter. Nitrogen release from urea in a mudball was slower than that from PU or SGU. Deep placed SCU released N at a markedly slower rate than MBU throughout 45 days after placement. Nitrogen release from deep placement sites of the different forms of urea appeared to be a diffusion‐controlled process.